Does Childcare Attendance Moderate the Associations Between Mother-Child Depressive Symptoms and Children's Peer Victimization Experiences? - Larose, Marie-Pier; Barker, Edward D.; Ouellet-Morin, Isabelle; Salmivalli, Christina; Côté, Sylvana M. (Journal of Child & Family Studies, 2024)
Peer victimization experiences is suggested to play a mediating role in the transmission of depression symptoms between mothers and children. Childcare attendance has been found to reduce the association between mother and child depressive symptoms. However, it is not clear whether this protective effect unfolds via a reduction of peer victimization experiences in middle childhood. The aims of this study were to test (1) whether peer victimization in middle childhood mediated the association between exposure to maternal depressive symptomatology in early childhood and child depressive symptoms in late childhood, (2) whether childcare attendance moderate the direct associations between maternal depressive symptoms and children's peer victimization experiences in middle childhood as well as depressive symptoms in late childhood and (3) whether childcare attendance moderates this mediated association. Data come from the Avon Longitudinal Study of Children and Parents (N = 5526) where exposure to maternal depressive symptoms and intensity of childcare attendance were assessed repeatedly during early childhood. Children's peer victimization and depressive symptoms were self-reported at eight and 10 years of age, respectively. We used weighted structural equation modeling and found that the association between mothers and children's depression was partially mediated by peer victimization. Childcare attendance did not moderate the indirect effect of maternal depression on child depressive symptoms via peer victimization. However, we found that for children who attended childcare, maternal depression was no longer associated child depressive symptoms in late childhood. In conclusion, peer victimization experiences partly explain the intergenerational transmission of depressive symptoms, but this mechanism is not altered by children's childcare attendance. Future research should examine potential socio-emotional and school readiness mechanisms that may break the cycle of depressive symptomatology from mothers to children. Highlights: Children's peer victimization experiences partially explained the association mothers' and children's depressive symptoms. Part-time childcare attendance decreased the association between mothers' and children's depressive symptoms. We did not find that childcare attendance moderated the association between mother's depressive symptoms and children's peer victimization experiences. The protective role of childcare attendance did not unfold via a reduction of peer victimization experiences, other intermediary psychosocial factors need to be explored.